Dietary Habits Based on Indonesian Dietary Guidelines During the Covid-19 Pandemic - Riyanto, Slamet; Asturiningtyas, Ika Puspita; Setianingsih, Ismi; Machfutra, Eka Denis (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2023)
Decreased immunity is a risk factor for viral respiratory infections, underscoring the crucial role of balanced diets to support the immune system. Therefore, this study aimed to determine the eating habits of people in the location based on balanced nutrition guidelines during the Covid-19 pandemic. A cross-sectional design was used and the samples included 3394 respondents who met the criteria of being ≥15 years old and living in the provinces of Central Java, East Java, Riau, and Southeast Sulawesi. Data were collected using a Google form-based online questionnaire filled out independently by respondents. The gathered data comprised compliance with balanced nutrition recommendations for consuming staples, protein-rich foods, fruits, vegetables, water, salt, sugar, and oil. In addition, diet was also observed based on several sociodemographic variables. The results showed that during the Covid-19 pandemic, 75.7% of respondents had not fulfilled intake according to balanced nutrition advice due to insufficient fruit consumption. However, about 60.6% consistently used dietary supplements, and 77.8% did not limit salt, sugar, as well as oil intake. The population at more risk of inadequate nutrition included younger age groups, males, those with low education, unemployed, and living in areas with high Covid-19 cases. This study concluded that during the Covid-19 pandemic, many Indonesians did not implement a diet based on the principles of balanced nutrition. Therefore, education on the importance of balanced nutrition consumption, local food campaigns, cheap markets, and food aid was needed, specifically for rarely consumed diets such as fruit, by targeting the most vulnerable groups.